2019
DOI: 10.1371/journal.pone.0220628
|View full text |Cite
|
Sign up to set email alerts
|

Using diphenyleneiodonium to induce a viable but non-culturable phenotype in Mycobacterium tuberculosis and its metabolomics analysis

Abstract: Depletion of oxygen levels is a well-accepted model for induction of non-replicating, persistent states in mycobacteria. Increasing the stress levels in mycobacterium bacilli facilitates their entry into a non-cultivable, dormant state. In this study, it was shown that diphenyleneiodonium, an inhibitor of NADH oxidase, induced a viable, but non-culturable state in mycobacteria, having similar features to dormant bacilli, like loss of acid-fastness, upregulation of stress-regulated genes and decreased superoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
(73 reference statements)
1
7
1
Order By: Relevance
“…Figure 2 shows the DPI treatment results for the induction of VBNC state in H37Rv and H37Ra (18). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows the DPI treatment results for the induction of VBNC state in H37Rv and H37Ra (18). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, NADH oxidase inhibitor diphenyleneiodonium chloride (DPI) was reported to simply and rapidly induce a VBNC state in the Mtb H37Ra strain, and incubation with fetal bovine serum, which is a common supplement for mammalian cell cultures, could facilitate the reactivation of VBNC cells, while incubation with OADC (oleate-albumin-dextrose-catalase) supplementation could not (18). This report gave us an important clue for constructing a simple and rapid assay system to induce and reactivate VBNC Mtb cells.…”
Section: Bsa Promotes Reactivation Of Vbnc M Tuberculosismentioning
confidence: 99%
“…As such, DPI treatment may induce a viable but nonculturable (VBNC) state in T. vaginalis . DPI has been similarly reported to induce the rapid transition from an active to a VBNC state in Mycobacterium tuberculosis [ 40 ]. Collectively, these data strongly suggest that DPI contribute to parasite detachment from host cells during T. vaginalis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Lau SKP et al [10] reported that the content of 24 metabolites in the culture supernatant of M. tuberculosis was significantly higher than that of non- M. tuberculosis group, of which 4 metabolites were identified as 1-tuberculin adenosine derivatives, which may be used as a new marker of metabolism of M. tuberculosis . Yeware A et al [11] focused on the mechanism of rapid transition of M. tuberculosis from the active state to the viable but non-culturable state caused by ammonium diphenylene alkylate treatment through metabolomics and compared it with the dormant phenotype.…”
Section: Introductionmentioning
confidence: 99%